Development of Non-Cognitive Diagnostic Assessment based on Google Sites in Chemistry Learning for Students - Agusta, Muhammad Farras Leonasa; Hairida, Hairida; Enawaty, Eny (Universitas Pendidikan Mandalika, 2025)
This study aims to measure the level of validity and response of educators and students to non-cognitive diagnostic assessments based on google sites in chemistry learning. This study's methodology is Research and Development (R&D) based on the ADDIE paradigm. Literature reviews, interviews, observations, and tests (validity instrument and response questionnaire) were used to gather data. The non-cognitive diagnostic test used in this study was based on google sites which was tested on 3 chemistry educators, 8 students of MA Al-Anwar Pontianak on a small scale, and 27 students of MA Islamiyah Pontianak on a large scale. The developed media was tested for validity in the aspects of assessment, media, and language by 5 assessment experts, 2 media experts, and 2 language experts respectively. The validity test results showed the percentage of feasibility in the assessment aspect was CVI 1.00, media 97%, and language 94%. The average percentage of chemistry educators responses to the developed media was 96% with a very good category, while the average percentage of students responses in the small-scale trial was 88% and the students response test in the large-scale trial was 87%. Thus, the non-cognitive diagnostic assessment based on google sites has a very valid validity category and a very good response so that it can be used to measure interest in learning chemistry.